Intelligent fault diagnosis of machinery using digital twin-assisted deep transfer learning - Xia, Min; Shao, Haidong; Williams, Darren; Lu, Siliang; Shu, Lei; de Silva, Clarence W. (Reliability engineering & system safety, 2021)
•A methodology for fault diagnosis with limited available data is achieved.•A digital twin of the machine is used to provide fault condition data for pre-training.•One-shot learning is achieved with the proposed deep transfer learning method.•Activation function and cost function of the deep network structure are improved. Digital twin (DT) is emerging as a key technology for smart manufacturing. The high fidelity DT model of the physical assets can produce system performance data that is close to reality, which provides remarkable opportunities for machine fault diagnosis when the measured fault condition data are insufficient. This paper presents an intelligent fault diagnosis framework for machinery based on DT and deep transfer learning. First, the DT model of the machine is built by establishing the simulation model and with further updating through continuously measured data from the physical asset. Second, all important machine conditions can be simulated from the built DT. Third, a new-type deep structure based on novel sparse de-noising auto-encoder (NSDAE) is developed and pre-trained with condition data from the source domain, as generated from the DT. Then, to achieve accurate machine fault diagnosis with possible variations in working conditions and system characteristics, the pre-trained NSDAE is fine-tuned using parameter transfer with only one sample from the target domain. The presented method is validated through a case study of triplex pump fault diagnosis. The experimental results demonstrate that the proposed method achieves intelligent fault diagnosis with a limited amount of measured data and outperforms other state-of-the-art data-driven methods.